Development and quality assessment of herb-flavored sweetpotato-chocolate - Hilapad, Marife R. (Passage Journal, 2014)
This study aimed to formulate and optimize the process of herb-flavored sweetpotato-chocolate spread. Plackett-Burman (PB) variable screening design and Response Surface Methodology (RSM) were used as experimental designs. A 33 factorial experiment arranged in Central Composite Design (CCD) with sweetpotato (125, 150, and 175 g), cocoa tablet (20, 25, and 30g) and basil (5, 10, and 15 g) were used as independent variables.